Evaluation of the DPPH Radical Scavenging Activity, Total Phenolic Content and Total Flavanoid Content of Different Solvent Extracts of Catunaregam tomentosa (Blume ex DC) Tirveng Leaves - Muhammad Yusran, Abdul Aziz; Ahmad Syibli, Othman; Syed Ahmad Tajudin, Tuan Johari (2021)
Catunaregam tomentosa (Blume ex DC) Tirveng is commonly known as Khet in Thailand and Bisa Ular or Badang in Malaysia. The tree is widely distributed in the north-east region of Thailand while in Malaysia the tree usually grows in the open waterfront area at Terengganu. This plant belongs to the Rubiaceae family, and the genus catunaregam has interesting pharmacological activities such as anti-inflammatory, antispasmodic, antidysenteric, antifertility and immunomodulatory. In this study, the leaves were extracted using dichloromethane, ethyl acetate and ethanol. Total phenolic was determined by FolinCiocalteau method are 115.0 ± 1.135, 340.8 ± 3.209 and 30.24 ± 1.702 mg GAE/g with dichloromethane, ethanol, and ethyl acetate, respectively. Total flavonoid was determined by the aluminium chloride calorimetric method are 47.01 ± 0.577, 56.78 ± 1.970 and 40.89 ± 1.079 mg QE/g with dichloromethane, ethanol, and ethyl acetate, respectively. Meanwhile, its antioxidant activity was evaluated by the 2,2- diphenyl-1-picrylhydrazyl (DPPH) assay. The ethanolic extract was found to have the highest percentages of phenolic and flavonoid content. The ethanolic extract also demonstrated strong DPPH scavenging activity with IC50 at 20.07 ± 0.51µg/mL.